2017
DOI: 10.3389/fimmu.2017.00219
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of FOXP3 TSDR Underlies the Impaired Suppressive Function of Tregs from Long-term Belatacept-Treated Kidney Transplant Patients

Abstract: Regulatory T cells (Tregs) are considered key players in the prevention of allograft rejection in transplanted patients. Belatacept (BLT) is an effective alternative to calcineurin inhibitors that appears to preserve graft survival and function; however, the impact of this drug in the homeostasis of Tregs in transplanted patients remains controversial. Here, we analyzed the phenotype, function, and the epigenetic status of the Treg-specific demethylated region (TSDR) in FOXP3 of circulating Tregs from long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Recent studies also confirmed that neither frequencies nor the suppressive function of Treg cells were impaired in ESRD patients before and after the initiation of dialysis . However, similar to our studies, Treg frequencies and Treg function were shown to be reduced in long‐term kidney transplant patients . Our findings indicate that, similar to aging or pregnancy, renal insufficiency may provoke diminished thymic output of RTE Treg/Tresp cells and therefore accelerated peripheral differentiation of these cells.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies also confirmed that neither frequencies nor the suppressive function of Treg cells were impaired in ESRD patients before and after the initiation of dialysis . However, similar to our studies, Treg frequencies and Treg function were shown to be reduced in long‐term kidney transplant patients . Our findings indicate that, similar to aging or pregnancy, renal insufficiency may provoke diminished thymic output of RTE Treg/Tresp cells and therefore accelerated peripheral differentiation of these cells.…”
Section: Discussionsupporting
confidence: 90%
“…We further showed that TNF induced CD25 expression in Treg cells and also increased IL‐2–induced CD25 and STAT5 phosphorylation in Treg cells. Phosphorylated STAT5 binds to demethylated CNS2, which contains the TSDR and thus may stabilize Foxp3 expression, leading to the high suppressive activity of Treg cells . On another note, the STAT5/STAT3 balance controls the fate of CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some groups reported no short- or long-term effects on Treg numbers and function when compared to treatment with CNIs [ 46 , 47 ], others reported a decrease in Treg and FoxP3 mRNA levels [ 48 ]. The only conclusion from clinical experience with CD28 blockade via CTLA4Ig, which could be agreed on, was the fact that induction of tolerance with CTLA4Ig and current concomitant regimens was unlikely [ 13 , 49 ]. In mouse models, on the other hand, CTLA4Ig treatment seems to be able to favor regulatory mechanisms in order to induce an operational tolerant state.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that CTLA4Ig does not negatively impact Treg conversion via TGF β in vitro , which in our opinion is of major relevance as it mimics the generation of allospecific pTregs in the periphery. Clinical data and murine studies suggest that in long-term kidney transplant patients, indirect allospecific T cells mainly contribute to late graft rejection [ 13 , 57 , 58 ]. As tTregs and pTregs are generally believed to represent distinct TCR repertoires, several reports have suggested a division of labor between those subsets [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation